Pengaruh Transparansi dan Akuntabilitas Laporan Keuangan Pemerintah Daerah (LKPD) Terhadap Tingkat Korupsi Pemerintah Daerah (Studi pada Pemerintah Kota Se-Sumatera) - Khairudin KHAIRUDIN; Rina Erlanda (Universitas Bandar Lampung (UBL), 2016)
This study aims to demonstrate empirically the effect of the transparency and accountability of local government financial statements (LKPD) on the level of local government corruption. Tests performed on 15 city government in Sumatera.The data used are secondary data derived from the results of the Corruption Eradication Commission (KPK) on National Integrity Index of local government, the local government website, and the results of the audit The Audit Board of the Republic of Indonesia (BPK RI) on the financial statements of local government in 2011 to the year 2013.This study using purposive sampling method and using a multiple linear regression analysis. The results showed that the transparency of local government financial statements (LKPD) negatively affect the level of local government corruption and accountability of local government financial statements (LKPD) positive effect on the level of local government corruption.